EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE STRUCTURED NUMBERED HEADS (SNH) DAN TWO STAY TWO STRAY (TSTS) PADA PEMAHAMAN KONSEP DAN PEMECAHAN MASALAH SISWA KELAS VII SMP NEGERI SURAKARTA DITINJAU DARI KECEMASAN SISWA PADA MATERI POKOK BANGUN DATAR - Alfonsa Maria Sofia Hapsari; Budiyono Budiyono; Riyadi Riyadi (Jurnal Pembelajaran Matematika, 2016)
Abstract: This research aims at determining the effect of learning models on conceptual understanding and problem-solving viewed from the  anxiety on mathematics. The learning models compared were TSTS, SNH, and direct instruction. This research used the quasi experimental research method. The proposed hypotheses of research were tested by using the two-way multivariate variance analysis with unbalanced cells. The results of research are as follows: 1) the cooperative learning model of the TSTS type gives a better conceptual understanding and problem solving than the cooperative learning model of the SNH type and the direct learning model, but both the cooperative learning model of the SNH type and the direct learning model give the same good conceptual understanding and problem solving; (2) the students with the low anxiety level on Mathematics have a better conceptual understanding and problem solving than those with the moderate anxiety level on Mathematics, and those with high anxiety level on Mathematics, and the students  with the moderate anxiety level on Mathematics have a better conceptual understanding and problem solving than those with the high anxiety level on Mathematics; (3) in the direct learning model, the students with the low anxiety on Mathematics have a better conceptual understanding and problem solving than those with the moderate anxiety level on Mathematics and those with the high anxiety level on Mathematics, but in the cooperative learning model of the SNH type and the cooperative learning model of the TSTS type, all of the groups of the students have the same good conceptual understanding and problem solving; and (4) in each anxiety level, the three learning models give the same good conceptual understanding and problem solving.Keywords: SNH, TSTS, problem solving, conceptual understanding